2020
DOI: 10.1039/d0cy01581d
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-driven photo-enhanced zinc–air batteries using synergistic effect of different types of MnO2 nanostructures

Abstract: Crystalline phases along with the morphology of any semiconducting material are the key factors which govern its photocatalytic properties. Herein, we have prepared a composite of α- and δ-MnO2 with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…As shown in Figure a, XPS survey spectra confirm the presence of Ti and O in TNRs and Bi, Ti, and O in all BTRs samples. The presence of carbon could be attributed to the adventitious or instrumental carbon Figure b shows the core-level spectra of Ti 2p and Bi 4d for TNRs and 20-BTRs catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure a, XPS survey spectra confirm the presence of Ti and O in TNRs and Bi, Ti, and O in all BTRs samples. The presence of carbon could be attributed to the adventitious or instrumental carbon Figure b shows the core-level spectra of Ti 2p and Bi 4d for TNRs and 20-BTRs catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of carbon could be attributed to the adventitious or instrumental carbon. 49 Figure 3b shows the core-level spectra of Ti 2p and Bi 4d for TNRs and 20-BTRs catalysts. From the XPS spectra of 20-BTRs, it has been observed that both Ti 2p and Bi 4d are having overlapping peaks, which are difficult to analyze.…”
mentioning
confidence: 99%
“…Various approaches have been adopted in order to decrease this large electric bias. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] They will be reviewed here below.…”
Section: Operation Principle Of Zn-air Batteriesmentioning
confidence: 99%
“…13 The Halder and Sawangphruk group also reported the importance of photoactive materials in enhancing the performances of the Zn−air batteries. 14 On the other hand, replacing the liquid electrolyte with the solid polymer electrolyte is an interesting approach to manage the abovementioned difficulties. Gel-based electrolytes will significantly help in preventing the accumulation of reaction products on the electrode surface and increasing the oxygen distribution, ultimately enhancing Li−O 2 battery efficiency.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Liu et al utilized solar energy to improve the OER rates in the Zn–air battery . The Halder and Sawangphruk group also reported the importance of photoactive materials in enhancing the performances of the Zn–air batteries. , …”
Section: Introductionmentioning
confidence: 99%